Insentif PPh Final UMKM Terdampak Covid-19: Studi Kasus pada KPP Pratama Jakarta Tanah Abang Satu - Wijastuti, Andita Meilia; Nuryanah, Siti (E-Jurnal Akuntansi, 2024)
The government issued an incentive policy for Government Borne Final Income Tax for MSME Taxpayers during the COVID-19 pandemic. The research aims to evaluate this policy based on the tax collection principle "The Four Maxims" and its implementation during the incentive period from April 2020 to December 2021. The research was conducted at Jakarta Tanah Abang Satu Tax Office. The research uses mixed methods with a concurrent triangulation model. The data used includes primary data in questionnaires to MSME Taxpayers and interviews with tax officers, as well as secondary data in the form of incentive data from the tax office. The research results show that based on the perception of MSME Taxpayers, the tax incentive policy fulfills the tax collection principle of "The Four Maxims". However, tax incentive data shows that incentive utilization is still relatively low. The level of compliance in fulfilling incentive realization reports is also not optimal. In implementing policies, some obstacles arise from the side of taxpayers and tax officers. This research is expected to contribute to the tax office to improve services and convenience for MSMEs in utilizing tax incentives. Keywords: The Four Maxims; Tax Incentives; MSMEs; COVID-19 pandemic